A Hilbert Integral-Type Inequality with Parameters - Shang Xiaozhou; Gao Mingzhe (International Journal of Mathematics and Mathematical Sciences)
A Hilbert-type integral inequality with parameters α and (α,λ>0) can be established by introducing a nonhomogeneous kernel function. And the constant factor is proved to be the best possible. And then some important and especial results are enumerated. As applications, some equivalent forms are studied.